##### Ads

related to: AEI

The determinant is: 1.

**aei**+ bfg + cdh - ceg - bdi - afh And you know this is...dh - (c+i)eg - (b+h)di - (a+g)fh 4. det =**aei**+ bfg + cdh - ceg - bdi - afh + gei + hfg + idh - ieg - hdi - gfh 5...1 Answers · Science & Mathematics · 05/06/2012

1) abc = def = ghi = adg = beh = cfi =

**aei**= ceg = λ Take all products containing e, def = beh =**aei**...1 Answers · Science & Mathematics · 17/01/2009

determinant of a 3x3 matrix is =

**aei**+ bfg + cdh - afh - bdi - ceg where the matrix variables are: [a b c] [d e f] [g h i]1 Answers · Science & Mathematics · 01/12/2010

... determinant of a 3x3 matrix in the form [a b c] [d e f] [g h i] is

**aei**+ bfg + cdh - afh - bdi - ceg. In your matrix, plugging in the...3 Answers · Science & Mathematics · 27/05/2009

..., ........jei + khc + lbf - lec - kbi - jhf x = ------------------------------------------- .......

**aei**+ bfg +cdh - gec - hfa - idb .......aki + jfg + cdl - gkc - dji - alf y...1 Answers · Science & Mathematics · 06/01/2008

...addition of \ diagonals minus / diagonals, in other words

**aei**+ bfg + cdh - bdi - afh - ceg. (Do you see why I mentioned \...1 Answers · Science & Mathematics · 26/01/2011

... = l a b c l . . . . . .l d e f l . . . . . .l g h i l . . . then lAl =

**aei**+ bfg +cdh - ceg - bdi - afh Then the determinant in this question equals...2 Answers · Science & Mathematics · 30/05/2016

..., AAE, AAI, AAO, AAU, AEA, AEE,

**AEI**, AEO,AEU etc. To do this you do the number of ...5 Answers · Science & Mathematics · 16/01/2009

...one unknown stack (BC) and one coin from the other unknown stack (F). ...if (

**AEI**) balances with (BCF), then the counterfeit must be within (DGH...9 Answers · Science & Mathematics · 18/08/2006

Umm...isn't that 24? d = (

**aei**+ bfg + cdh) - (gec + hfa + idb)**aei**= 0 bfg = 2 * 4 * 3 = 24 cdh = 0 gec = 0 hfa = 0 idb = 02 Answers · Science & Mathematics · 16/10/2008

##### Ads

related to: AEI